Efektivitas edukasi kesehatan menggunakan media booklet terhadap peningkatan kepatuhan minum obat pada penderita hipertensi:Literature Review - Yuliana Yuliana; Intan Rismayanti; Opik Opik; Sidik Permana; Yagis Nurul Mujieb; Lilis Lismayanti (CV. ALIM'SPUBLISHING, 2026)
Hypertension is a chronic non-communicable disease that poses a major challenge to global and Indonesian health. One of the problems in hypertension management is low compliance in taking antihypertensive medication, which risks causing serious complications such as stroke, heart failure, etc. Health education through booklets is considered effective as a promotive-preventive strategy because it is visual, easy to understand, and can be taken home by patients. The research method used a systematic review, where data sources came from Google Scholar and the Garuda portal. The selected articles have met the inclusion criteria with full-text articles that have been filtered for the last 5 years from 2021-2026. The results of the study show that health education using booklets is effective in increasing medication adherence in hypertension sufferers.